'What gets measured gets done' : Addressing Policy Capture and Privilege-Seeking in the MENA Region and Beyond - Akhtar, Mahmood Syed; Ait Ali Slimane, Meriem (World Bank, Washington, DC, 2018)
Countries around the globe are seeking to diversify their economies and make them competitive. For this to happen, resources need to flow to firms that can make the best use of them. This is not the case in many countries. A good example is the MENA region where, in many countries, the policy regime has evolved in a manner such that a small number of firms end up getting a disproportionate share of resources - public land, procurement contracts, energy, finance and investment incentives, to name a few - not because they are more efficient but because they are politically connected. This skewed distribution of productive resources is a major cause of the high unemployment rates in the region, especially for young graduates - ranging between 15 and 25 percent. In brief, the ones with resources do not create many jobs. The ones that could have created jobs do not get the resources to do so. Although ubiquitous in MENA, this problem afflicts many other countries. The prosperity and social cohesion of the MENA region still rests on its ability to transform its public administration to better deliver services to the private sector to absorb a young and increasingly well-educated labor force. This will particularly be the case in post conflict countries were social issues and stability concerns are more acute. Making policy areas resistant to privilege is important for this agenda. The complex political economy underlying policy capture and privilege-seeking may make this a seemingly intractable problem. However, the new study is inspired by recent literature on dynamics of policy change point to windows of opportunity within a complex political economy setting that allow incremental improvements with substantial cumulative effect over time. It breaks new ground by applying, to the private sector governance space, the motto “What gets measured gets done”